2020
DOI: 10.1101/2020.02.28.961391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TP53abnormalities correlate with immune infiltration and are associated with response to flotetuzumab, an investigational immunotherapy, in acute myeloid leukemia

Abstract: Purpose: Somatic TP53 mutations and 17p deletions with genomic loss of TP53 occur in 37-46% of acute myeloid leukemia (AML) cases with adverse risk cytogenetics and are associated with primary induction failure (PIF), high risk of relapse and dismal prognosis. Herein, we aimed to characterize the immune landscape of TP53 mutated AML and to determine whether TP53 abnormalities identify a patient subgroup that may benefit from T-cell targeting immunotherapy approaches. Experimental Design: The NanoString Pan-Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…As proof-of-principle activity of immunomodulatory therapy in TP53 mutant AML, recent data with the CD3xCD123 DART flotetuzumab showed antileukemic activity in 5 of 11 patients. 43 We have provided evidence that the mir34a-MYC-PD-L1 signaling cascade is involved in enhanced PD-L1 expression in patients with TP53 mutations, but we acknowledge that there are other pathways involved in the upregulation of PD-L1, including other transcription factors that can bind and transactivate PD-L1, such as HIF1-a, NF-kB, AP-1, STAT 1/3, and that further exploration of these factors in MDS/AML is warrented. 44 Objective responses to immune checkpoint therapy have been observed in only a small subset of patients with MDS/sAML, and insight into which subgroups may best benefit from immunotherapy is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…As proof-of-principle activity of immunomodulatory therapy in TP53 mutant AML, recent data with the CD3xCD123 DART flotetuzumab showed antileukemic activity in 5 of 11 patients. 43 We have provided evidence that the mir34a-MYC-PD-L1 signaling cascade is involved in enhanced PD-L1 expression in patients with TP53 mutations, but we acknowledge that there are other pathways involved in the upregulation of PD-L1, including other transcription factors that can bind and transactivate PD-L1, such as HIF1-a, NF-kB, AP-1, STAT 1/3, and that further exploration of these factors in MDS/AML is warrented. 44 Objective responses to immune checkpoint therapy have been observed in only a small subset of patients with MDS/sAML, and insight into which subgroups may best benefit from immunotherapy is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…A study from 2018, conducted on 55 patients, demonstrated that the incidence of PD-L1 expression is higher in patients with leukocytosis [30]. Other studies showed a correlation between TP53 mutation and the overexpression of PD-L1 [2,104].…”
Section: Results In Amlmentioning
confidence: 99%
“…14,15 Importantly, TP53 mutant AML patients have been strongly associated with an adverse immune microenvironment and potentially may be an optimal molecular subset for novel immunomodulatory agents. 16…”
Section: Resultsmentioning
confidence: 99%